KEWALIAN DALAM TASAWUF NUSANTARA - Yunasril Ali (Sekolah Tinggi Agama Islam Sadra, 2013)
This article discusses the doctrine of Sainthood (al-walāyah) which has a strong basis in the Qur’an and ḥadīth and it has been elaborated systematically through Ibn ‘Arabi’s vast and complex teachings. While in the study of Sufism in the archipelago, the term saint (walī)has been known along with the spread of Islam began in the archipelago, and it refers to two meanings; as the person who has the occulties as the implications of the sanctity and walī as the ruler of a particular region. Regardless the definition and scope, the true doctrine of sainthood can not be separated from the teaching of the prophetic and apostolic message which implies the human world is not only the physical realm, but there is a metaphysical world that has not been known to human and from which the physical world is controlled.